Perception and satisfaction regarding breast feeding among breast feeding mothers: a hospital based study - Prakash, Vimarshitha; R., Sheela S.; Raj, Krithika; Satyanarayana, Pradeep Tarikere (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: World Health organization (WHO) states that to ensure child health and survival, Breast feeding can be best tool. It also mentions that nearly 2 out of 3 are not exclusively breast fed and a special note that only 41 % are exclusively breast fed for 6 months. Breastfeeding satisfaction is defined as, “the satisfying feeling obtained during breastfeeding resulting from cooperation between the mother and the infant to fulfill desires or needs”. Methods: This was a hospital based cross sectional study carried at Department of Obstetrics and Gynecology, Sri Devaraj Urs Medical College, SDUAHER, Kolar from December 2019 to August 2020 for a period of 10 months. Sample size was calculated based on previous study. Results: The present study was a cross sectional study carried out for a period of 9 months at SDUMC tertiary care center. 270 mothers were part of study among which 82 (30.3%) had completed high school, 110 (40.7%) belonged to 21-25 years, 184 (68.07%) were Hindus, 125 (46.2%) belonged to Upper middle class of Modified BG Prasad’s classification 2019, 199 (73.6%) had delivered through normal delivery and 142 (52.7%) had more than one child. Out of 270 breast feeding mothers, 214 (79.3%) has satisfactory knowledge, 148 (54.8%) had satisfactory attitude and only 47 (17.4%) had satisfactory practice. Mothers having higher education status, having more than one child, home makers and those delivered by Normal delivery had higher scores were statistically significant. Conclusions: Perceptions regarding breast feedings were not satisfactory at various segments and breast feeding satisfaction were influenced by education, working status, number of children and family members were significant factors influencing breast feeding satisfaction.